Involvement of Caveolin-1 in repair of DNA damage through both homologous recombination and non-homologous end joining. - Hua Zhu; Jingyin Yue; Zui Pan; Hao Wu; Yan Cheng; Huimei Lu; Xingcong Ren; Ming Yao; Zhiyuan Shen; Jin-Ming Yang (PLoS ONE, 2010)
Caveolin-1 (Cav-1), the major component of caveolae, is a 21-24 kDa integral membrane protein that interacts with a number of signaling molecules. By acting as a scaffolding protein, Cav-1 plays crucial roles in the regulation of various physiologic and patho-physiologic processes including oncogenic transformation and tumorigenesis, and tumor invasion and metastasis.In the present study we sought to explore the role of Cav-1 in response to DNA damage and the mechanism involved. We found that the level of Cav-1 was up-regulated rapidly in cells treated with ionizing radiation. The up-regulation of Cav-1 following DNA damage occurred only in cells expressing endogenous Cav-1, and was associated with the activation of DNA damage response pathways. Furthermore, we demonstrated that the expression of Cav-1 protected cells against DNA damage through modulating the activities of both the homologous recombination (HR) and non-homologous end joining (NHEJ) repair systems, as evidenced by the inhibitory effects of the Cav-1-targeted siRNA on cell survival, HR frequency, phosphorylation of DNA-dependent protein kinase (DNA-PK), and nuclear translocation of epidermal growth factor receptor (EGFR) following DNA damage, and by the stimulatory effect of the forced expression of Cav-1 on NHEJ frequency.Our results indicate that Cav-1 may play a critical role in sensing genotoxic stress and in orchestrating the response of cells to DNA damage through regulating the important molecules involved in maintaining genomic integrity.